2019
DOI: 10.1111/1471-0307.12615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different coagulants on the yield, sensory, instrumental colour and textural characteristics of cow's milk Paneer

Abstract: Paneer was prepared from cow's milk (4.5% fat and 8.5% SNF) using five coagulants, viz. citric acid (CA), malic acid (MA), alum (AL), calcium lactate (Ca-L) and glucono-delta-lactone (GDL). Among these, GDL and MA exhibited similar effects on colour and appearance, flavour as well as overall acceptability. The yields of Paneer were 158. 09, 183.71, 201.11, 206.34 and 188.83 g/L of milk for the above coagulants, respectively. All Paneer samples showed higher values of hardness, cohesiveness, springiness and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…The recorded results are in concord with the findings of Dwivedi et al (2010) in paneer spread, Raj (2013) in chhana spread, Sharma and Jaseja (2016) in paneer spread, Yadav and Wadehra (2016) in paneer, Kumar (2017) in cow milk paneer, Kaur (2019) for paneer spread, Prajapat (2019) in paneer, Wanjari et al (2019) in garlic treated paneer, Singh et al (2020) in khoa burfi and Devi et al (2021) in milk nuggets who reported that the similar trend of significant increase (P<0.01) in the standard plate count with increase of storage period. The findings of study are in contradiction with Tak et al (2018) in yoghurt who observed the significant decrease (P<0.01) in the standard plate count with increase of storage period.…”
Section: Standard Plate Count (Spc) Of Paneer Spreadsupporting
confidence: 88%
See 1 more Smart Citation
“…The recorded results are in concord with the findings of Dwivedi et al (2010) in paneer spread, Raj (2013) in chhana spread, Sharma and Jaseja (2016) in paneer spread, Yadav and Wadehra (2016) in paneer, Kumar (2017) in cow milk paneer, Kaur (2019) for paneer spread, Prajapat (2019) in paneer, Wanjari et al (2019) in garlic treated paneer, Singh et al (2020) in khoa burfi and Devi et al (2021) in milk nuggets who reported that the similar trend of significant increase (P<0.01) in the standard plate count with increase of storage period. The findings of study are in contradiction with Tak et al (2018) in yoghurt who observed the significant decrease (P<0.01) in the standard plate count with increase of storage period.…”
Section: Standard Plate Count (Spc) Of Paneer Spreadsupporting
confidence: 88%
“…The statistical analysis revealed that a highly significant difference (P<0.01) between treatment, between period and interaction between treatment and period. The results are in agreement with Raj (2013) in chhana spread, Yadav and Wadehra (2016) in paneer, Kumar (2017) in cow milk paneer, Kaur (2019) in paneer spread, Wanjari et al (2019) in garlic treated paneer, Prajapat (2019) in paneer, Singh et al (2020) in khoa burfi and Devi et al (2021) in milk nuggets who reported increase in yeast and mould count during storage.…”
Section: Yeast and Mould Count Of Paneer Spreadsupporting
confidence: 87%
“…Paneer, as a very popular heat‐acid coagulated product of milk in India and in many other parts of the world, is a highly rich source of nutrition for good quality protein, fat, vitamins and minerals like calcium and phosphorus (Dey et al, 2020; Kumar, Mishra, Sutariya, Chaudhary, & Rao, 2019). It is used in various culinary dishes and snack items throughout the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…The hardness and chewiness of Paneer samples were determined by the two‐bite linear compression method (Kumar et al . 2019) using a texture analyser (TA‐XT plus; Stable Microsystems, Godalming, UK) fitted with a 50 kg load cell. A circular disc probe of 75 mm (P/75) diameter was attached to the cross‐head of the machine.…”
Section: Methodsmentioning
confidence: 99%